L'Assunzione di Maria e la gloria dei santi alla luce della Scrittura un'ipotesi biblica ed ecumenica - Rossetti, Carlo Lorenzo 1967- (2025)
The article proposes the hypothesis that in favor of the dogma of the glorification of the Virgin Mary three biblical texts could be adduced which are not yet used in the Catholic Magisterium. It is Mat 27:52-53; 2Cor 5:1-5 and Rev 20:4-6. This biblical expansion strengthens Catholic doctrine and makes it more ecumenical, but at the same time it demands a renewed conception of the immediate post-mortem destiny of the martyrs and saints.
Keywords: Assumption of Mary; Eschatology; Resurrection; Munificentissimus Deus; Mat 27; 2Cor 5; Rev 20